Elevated butyric acid and histamine in feces and serum as an indicator of onset of necrotic enteritis in broiler chickens - Gautam, Hemlata; Ahmad, Shaik Noor; Banaganapalli, Babajan; Popowich, Shelly; Chow-Lockerbie, Betty; Ayalew, Lisanework E.; Mandal, Rupasri; Wishart, David S.; Tikoo, Suresh; Gomis, Susantha (Frontiers in Microbiology, 2025)
BackgroundClostridium perfringens (CP) induced necrotic enteritis (NE) is an economically significant intestinal disease of broiler chickens. Identifying potential biological markers during the development of NE might facilitate early disease control measures. Therefore, the current study aimed to identify the metabolites and metabolic pathways changes associated with the onset of NE in serum and feces of CP-infected broiler chickens.MethodologyThe protein content of the feed was abruptly altered from 20% to 28% using a well-established NE model before challenging the birds with CP. Then, we performed a targeted, fully quantitative liquid chromatography-tandem mass spectrometry (LC-MS/MS) -based assay for analyzing the metabolomics profile of serum, feces, and jejunal contents in NE birds. The data were analyzed to understand the trend of metabolite distribution, relationships between metabolites and pathway impacts.ResultsBirds with NE showed metabolic variations including lipids, amino acids, and organic acids, across all the biological samples analyzed. This variation was higher in serum samples (310/597 metabolites, 51.92%), compared to fecal (182/608 metabolites, 29.93%), and jejunal samples (125/607 metabolites, 20.59%). A robust statistical analysis of these metabolites identified 19 common metabolites, including butyric acid and histamine. Pathway analysis identified that six of them were enriched in key pathways, like tricarboxylic acid cycle (TCA cycle) (citric acid and cis-aconitic acid), glyoxylate and dicarboxylate metabolism (citric acid and cis-aconitic acid), arginine-proline metabolism (spermine and creatinine), butanoate metabolism (butyric acid), and histidine metabolism (histamine). These pathways were related to energy synthesis, nitrogen metabolism, and immune response in NE birds.ConclusionThis study highlights metabolic differences in birds with NE and underscores butyric acid and histamine as potential early biomarkers for NE diagnosis. The upregulation of these metabolites across serum, jejunal and fecal samples reflects their local and systemic impacts on the disease. These biomarkers play key roles in several NE hallmark features, including gut barrier disruption, dysbiosis of microbes and tissue injury through immune system activation, and systemic inflammation. Future studies need to validate our findings across field conditions and different predisposing factors.